Charisiana III (Char. Gramm. p. 153.30 y p. 162.19 Barwick) - Marcos A. Pérez Alonso; Ramón Gutiérrez González (Exemplaria Classica, 2009)
This paper revises the text of two passages in the grammarian Charisius (Char. gramm. p.153.30 and p.162.19 Barwick). Both of them are taken from Iulius Romanus and include quotations from earlier grammarians. In the first, our conjecture removes the very rare construction of inquam with the infinitive, which has wrongly been ascribed to the elder Pliny on the basis of this passage. In the second, the restoration of the manuscript reading makes it very likely that Pliny’s Dubius sermo is the source for the passage.